Correlation between lower limb asymmetry and performance in professional female soccer players - de Freitas, Fabio Henrique (2024)
The structure of a soccer match is predominantly intermittent, characterised by synchronised and concomitant execution of low and high-intensity actions at different moments of the game, such as jumping, performing successive sprints and change of direction (COD). Furthermore, the repetition of such actions can contribute to the development of lower limb strength asymmetry. The objective of the present study was to investigate the relationship between lower limb asymmetry on peak concentric torque (PTCON) of the hamstrings and quadriceps muscles at 60°/s with performance in the 20-meter sprint, repeated anaerobic sprint test (RAST) and change of direction test (COD) in professional female soccer players. The sample consisted of twenty-two professional female soccer players from a first-division club in Brazilian football. Two visits were carried out with an interval of 48 hours between them. In addition, a value of p < 0.05 was adopted for statistical significance. The results showed no significant correlations between limb asymmetry in quadriceps PTCON, time and speed in the 20-meter sprint, time and velocity in the COD test, and total time in the RAST. Furthermore, no significant correlations were observed between limb asymmetry in hamstring PTCON, time and speed in the 20-meter sprint, time and velocity in the COD test, and total time in the RAST. Asymmetry in lower limb strength may not influence physical performance in sprints and COD tasks such as those adopted in the present study.